New approach for thickness determination of solution-deposited graphene thin films - Jussila, Henri; Albrow Owen, Tom; Yang, He; Hu, Guohua; Granqvist, Niko; Lipsanen, Harri; Howe, Richard C. T.; Sun, Zhipei; Hasan, Tawfique; AKŞİMŞEK, HÜSEYİN SİNAN (Amer Chemical Soc, 1155 16th St, Nw, Washington, Dc 20036 USA, 2017)
Solution processing-based fabrication techniques such as liquid phase exfoliation may enable economically feasible utilization of graphene and related nanomaterials in real-world devices in the near future. However, measurement of the thickness of the thin film structures fabricated by these approaches remains a significant challenge. By using surface plasmon resonance (SPR), a simple, accurate, and quick measurement of the deposited thickness for inkjet-printed graphene thin films is reported here. We show that the SPR technique is convenient and well-suited for the measurement of thin films formulated from nanomaterial inks, even at sub-10 nm thickness. We also demonstrate that the analysis required to obtain results from the SPR measurements is significantly reduced compared to that required for atomic force microscopy (AFM) or stylus profilometer, and much less open to interpretation. The gathered data implies that the film thickness increases linearly with increasing number of printing repetitions. In addition, SPR also reveals the complex refractive index of the printed thin films composed of exfoliated graphene flakes, providing a more rigorous explanation of the optical absorption than that provided by a combination of AFM/profilometer and the extinction coefficient of mechanically exfoliated graphene flakes. Our results suggest that the SPR method may provide a new pathway for the thickness measurement of thin films fabricated from any nanomaterial containing inks.
Keywords: Surface-Plasmon Resonance; Phase Exfoliation; Layer Graphene; Optoelectronics; Metamaterials; Electronics; Photonics; Graphite